Julian Steward and the Great Basin : the making of an anthropologist - Clemmer, Richard O.; Myers, L. Daniel, 1949-; Rudden, Mary Elizabeth, 1974- (University of Utah Press, 1999)
"Julian Steward and the Great Basin is a critical assessment of Steward's work, the factors that influenced him, and his deep effect on American anthropology. Steward (1902-1972) was one of the foremost American exponents of cultural ecology, the idea that societies evolve in adaptation to their human and natural environments. He was also central in shaping basic anthropological constructs such as "hunter-gatherer" and "adaptation." But his fieldwork took place almost entirely in the Great Basin of California, Nevada, and Utah."--BOOK JACKET. "Julian Steward and the Great Basin also corrects long-standing misperceptions that originated with Steward about lifeways of the Indians living between the Great Plains and California. It charts new directions for research, demanding a more exacting study of environmental conditions, material adaptations, and organizational responses, as well as an appreciation of the ideological and humanistic dimensions of Basin life."--Jacket